Dissolved Oxygen in the East Bolaang Mongondow Waters, North Sulawesi - Patty, Simon I.; Rizqi, Marenda Pandu; Huwae, Rikardo (Jurnal Ilmiah Platax, 2022)
Oxygen in seawater comes from the air through diffusion and photosynthesis. This study aims to determine the dissolved oxygen content, NAEC (Normal Atmospheric Equilibrium Concentration), and AOU (Apparent Oxygen Utilization) in East Bolaang Mongondow waters. The analysis showed that the dissolved oxygen content in the surface layer ranged from 6.01-7.05 mg/l; 5.91-6.98 mg/l (5 m depth); and 5.75-6.90 mg/l (near bottom depth). NAEC is closely related to water temperature and implicitly increases with depth. The highest NAEC value of 5.90 mg/l (t=28.0ºC) was found at the bottom depth, and the lowest NAEC of 5.63 mg/l (t=30.0ºC) was found at the surface layer. The dissolved oxygen saturation level of more than 100% and the average positive AOU value at 0.59-0.81 mg/l describe the amount of oxygen available in the surface layer.Keywords: Dissolved Oxygen; Normal Atmospheric Equilibrium Concentration (NAEC); Apparent Oxygen Utilization (AOU); East Bolaang Mongondow.AbstrakOksigen dalam air laut bersumber dari udara melalui proses difusi dan hasil fotosintesis. Penelitian ini bertujuan untuk mengetahui kandungan oksigen terlarut, NAEC (normal atmospheric equilibrium concentration) dan AOU (apparent oxygen utilization) di perairan Bolaang Mongondow Timur. Hasil analisis menunjukkan bahwa kandungan oksigen terlarut di lapisan permukaan berkisar antara 6,01-7,05 mg/l; kedalaman 5 meter 5,91-6,98 mg/l dan dekat dasar 5,75-6,90 mg/l. NAEC sangat berhubungan dengan suhu air dan secara implisit konsentrasinya akan semakin tinggi dengan bertambahnya kedalaman. Nilai NAEC tertinggi 5,90 mg/l (t=28,0ºC) ditemukan pada kedalaman dekat dasar dan  NAEC terendah 5,63 mg/l (t=30,0ºC) ditemukan pada lapisan permukaan. Tingkat kejenuhan oksigen terlarut >100 % dan rata-rata nilai AOU positif (0.59-0.81 mg/l) menggambarkan banyaknya kandungan oksigen yang tersedia pada lapisan permukaan.Kata kunci: oksigen terlarut; normal atmospheric equilibrium concentration (NAEC); apparent oxygen utilization (AOU); Bolaang Mongondow Timur.